Pengembangan media pembelajaran dekstop menggunakan aplikasi netbeans pada materi persamaan garis lurus - Kris Priyanto; Adi Nurjaman; Indah Puspita Sari (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The aim of the research is to develop learning media that are approprited and effective for use against mathematical understanding abilities in accordance with problem based learning steps and to find out the constraints encountered during the development process, this is done because of a lack of understanding of students in learning and a lack of use of learning media at school. The research method used was 4D R&D research and development which was modified to 3D (Define, Design, Develop) 44 (forty four) class VIII students as participants in the area test and product test, besides that supervisor I and II are also needed as validators. The results of this study are that the learning media developed are in accordance with the 3D R&D method, the learning media are appropriate and partical based on the validators and student responses which make learning media able to be implemented in class and the learning media used are effective and can be used students in 2 (two) class at one of the MTS in West Bandung Distric.